The Role of the Financial Services Authority (OJK) in Increasing Public Trust in Investment in Indonesia - Kemala Dewi; Arya Arwanda; Muhammad Albahi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the role of the Financial Services Authority (OJK) in increasing public trust in investment in Indonesia. As an independent institution, OJK has a strategic function in supervising and regulating the entire financial services sector, including the capital market, banking, and non-bank financial industry. Public trust is a key element in creating a healthy and sustainable investment climate. Through strict supervision policies, public education, and law enforcement against illegal investment violations, OJK seeks to strengthen the foundation of public trust. One of the concrete steps is the issuance of POJK No.17/2022 concerning the Code of Conduct for Investment Managers. This study uses a literature study method with a descriptive qualitative approach. The results of the study show that OJK's efforts in increasing transparency, expanding financial literacy, and taking firm action against illegal investment practices have made a significant contribution to increasing public trust. However, challenges such as low financial literacy and rampant investment fraud are still obstacles that need to be overcome. Therefore, synergy is needed between the OJK, the government, and the community to build a safe and reliable investment ecosystem. This research provides the implication that strengthening regulations, continuous education, and cross-sector collaboration are important strategies in maintaining the stability and integrity of the investment sector in Indonesia.